Regulation of mammalian Shaker-related K(+) channels: evidence for non-conducting closed and non-conducting inactivated states - Jäger, Heike (Blackwell Science Inc, 1998)
1. Using the whole-cell recording mode we have characterized two non-conducting states in mammalian Shaker-related voltage-gated K(+) channels induced by the removal of extracellular potassium, [Formula: see text]. 2. In the absence of [Formula: see text] , current through Kv1.4 was almost completely abolished due to the presence of a charged lysine residue at position 533 at the entrance to the pore. Removal of [Formula: see text] had a similar effect on current through Kv1.3 when the histidine at the homologous position (H404) was protonated (pH 6.0). Channels containing uncharged residues at the corresponding position (Kv1.1: Y; Kv1.2: V) did not exhibit this behaviour. 3. To characterize the nature of the interaction between Kv1.3 and [Formula: see text] concentration ([K(+)](o)), we replaced H404 with amino acids of different character, size and charge. Substitution of hydrophobic residues (A, V and L) either in all four subunits or in only two subunits in the tetramer made the channel insensitive to the removal of [Formula: see text] , possibly by stabilizing the channel complex. Replacement of H404 with the charged residue arginine, or the polar residue asparagine, enhanced the sensitivity of the channel to 0 mm [Formula: see text] , possibly by making the channel unstable in the absence of [Formula: see text]. Mutation at a neighbouring position (400) had a similar effect. 4. The effect of removing [Formula: see text] on current amplitude does not seem to be correlated with the rate of C-type inactivation since the slowly inactivating G380F mutant channel exhibited a similar [K(+)](o) dependence as the wild-type Kv1.3 channel. 5. CP-339,818, a drug that recognizes only the inactivated conformation of Kv1.3, could not block current in the absence of [Formula: see text] unless the channels were inactivated through depolarizing pulses. 6. We conclude that removal of [Formula: see text] induces the Kv1.3 channel to transition to a non-conducting ‘closed’ state which can switch into a non-conducting ‘inactivated’ state upon depolarization.